Peroxiredoxins are involved in the pathogenesis of multiple sclerosis and neuromyelitis optica spectrum disorder. (23rd July 2020) - Uzawa, A; Mori, M; Masuda, H; Ohtani, R; Uchida, T; Aoki, R; Kuwabara, S
Summary: Peroxiredoxins (PRXs) are intracellular anti-oxidative enzymes but work as inflammatory amplifiers under the extracellular condition. To date, the function of PRXs in the pathogenesis of multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) is not fully understood. The aim of this study was to investigate whether PRXs play a role in the pathogenesis of MS and NMOSD. We analyzed levels of PRXs (PRX1, PRX5 and PRX6) in the cerebrospinal fluid (CSF) and serum of 16 patients with MS, 16 patients with NMOSD and 15 patients with other neurological disorders (ONDs). We identified potential correlations between significantly elevated PRXs levels and the clinical variables in patients with MS and NMOSD. Additionally, pathological analyses of PRXs (PRX1-6) in the central nervous system (CNS) were performed using the experimental autoimmune encephalomyelitis (EAE), animal model of MS. We found that serum levels of PRX5 and PRX6 in patients with MS and NMOSD were higher compared with those in patients with ONDs ( P < 0·05). Furthermore, high levels of PRX5 and PRX6 were partly associated with blood–brain barrier dysfunction and disease duration in NMOSD patients. No significant elevation was found in CSF PRXs levels of MS and NMOSD. Spinal cords from EAE mice showed remarkable PRX5 staining, especially in CD45 + infiltrating cells. In conclusion, PRX5 and PRX6 may play a role in the pathogeneses of MS and NMOSD. Graphical Abstract: